Implementasi 4QC Tools Dan IOT Sebagai Pengendali Kegagalan Produk Usaha Batik Fendy, Klaten - Lilia Pasca Riani; Arwan Nur Ramadhan (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The study was conducted to identify the types of product defects, monitor the production process, and map the causes of product defects in the Batik Fendy Klaten Business, Central Java. The analysis method is carried out in 4 stages, namely making a histogram, pareto diagram, analyzing the control map p, and mapping the cause of product defects with a fishbone diagram. Primary and secondary data analysis in the form of data on the number of production and the number of defective products from November 2018 to October 2019. The results showed that the torn cloth is a dominant type of disability with a percentage of 32% of the total product defects, depicting the control chart p there are 7 out of 12 observation periods occurred processes that exceed the lower control limit, namely in November, December 2018, May, September, and October 2019 are under the lower control limit, whereas in November 2018, February, March and April 2019 are above the upper control limit, identification of the causes is found carelessness, manual method of cutting, material not according to criteria, and hot ambient temperature galvalume.